Doxycycline: An Antibiotic Attenuates Oxidant Stress, Perturbation of Lipid Metabolites, and Antioxidants against Vanadium Toxicity in Rat Hepatocytes - Gassar, Ezeddin Salem; Mohamed, Negia Abdullah Emtawel; Emtawel, Fatema Abdullah; Elfakhri, Rehab M.; Haider, Syed Saleem (Libyan International Medical University Journal, 2022)
Background The liver is target following exposure to pentavalent vanadium (V5+). Doxycycline is an antioxidant that prevents the progression of disease through inhibition of lipid peroxidation.Aim The present study was designed to evaluate the protective effects of doxycycline against vanadium-induced hepatoxicity.Methods Sixty two male Sprague-Dawley rats (250–300 g) were equally divided into the following four groups: control group (received 0.2 mL of physiological saline), doxycycline control group (received 4 mg/kg body weight on day 1 and 2 mg/kg body weight daily thereafter), vanadium group (received elemental vanadium 1.5 mg/kg-body weight in distilled water), and concomitantly treated group (doxycycline + vanadium) received (doxycycline 4 mg/kg body weight on day 1 and 2 mg/kg body weight thereafter + vanadium 1.5 mg/kg body weight), all given orally for 10 consecutive days. The rats were sacrificed by decapitation 24 hours after the last dose. The liver was removed rapidly and processed for the evaluation of metabolic variables: phospholipids, cholesterol, cerebrosides, gangliosides, reduced glutathione (GSH), vitamin C, calcium, acetylcholinesterase enzyme, and lipid peroxidation.Results Vanadium administration significantly reduced (−60 g) the body weight and significantly increased (+28%) the relative liver weight compared with controls. The rats exhibited neurological function deficits. Vanadium administration decreased the concentrations of metabolic variables compared with controls, cerebrosides (−50%), cholesterol (−39%), phospholipids (−18%), GSH (−45%), and inhibited acetylcholinesterase enzyme (–48%). Gangliosides (+ 38%), vitamin C (+ 20%), and calcium (+ 80%) were increased together with an enhancement (+64%) in lipid peroxidation. The combined treatment (vanadium and doxycycline) significantly increased (+25 g) the body weight and relative liver weight of rat was significantly reduced (+5%) compared with vanadium administered group. The levels of metabolic variables were significantly reversed in this group in the following order: cholesterol (+17%), phospholipids (+7%), vitamin C (−14%), acetylcholinesterase enzyme activity (−27%) together with inhibition (−16%) of lipid peroxidation. All levels were (p < 0.05). Doxycycline presented no effect on the levels of GSH, cerebrosides, and gangliosides.Conclusion Results of this study suggested vanadium-induced oxidation of lipids and sphingolipids in hepatocytes and much of GSH was consumed against high production of reactive oxygen species. Doxycycline protected against vanadium-induced oxidative damage that could be attributed to its free radical scavenging effects on membrane-bound lipids and acetylcholinesterase enzyme.
Keywords: vanadium; doxycycline; lipid profiles; lipid peroxidation; glutathione; ascorbic acid; acetylcholinesterase